Hydroxyapatite Lanthanum Oxide Composites - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2015)
In the present study a commercially synthetic hydroxyapatite powders (CSHAp) were doped with lanthanum oxide (5 and 10 wt.% La2O3). The composite powders were well homogenized and pelleted in an uniaxial mould at 350 MPa. Pelleted green bodies were sintered at five different temperatures. Finally, the effect of La2O3 amount on the microstructural and mechanical properties of CSHA was investigated. Microstructural properties were detected by X-ray diffraction patterns (XRD) and scanning electron microscope (SEM). Mechanical properties of the sintered samples were determined by the density, hardness and compression strength measurements. Experimental results show that the mechanical properties of HA can be improved by the doping of La2O3
Keywords: MECHANICAL-PROPERTIES; BOVINE HYDROXYAPATITE; BONE